Euphorbia kadapensis (Euphorbiaceae), a new species from southern India - Sarojinidevi, Naidu; Reddivenkataraju, Rudraraju (Phytotaxa, 2014)
Euphorbia kadapensis, a new species of Euphorbiaceae is described from Kadapa district in Rayalaseema region of Andhra Pradesh, southern India. It belongs to Euphorbia subgen. Chamaesyce. Within the group, it resembles E. concanensis, E. longistyla and E. senguptae of sect. Anisophyllum subsect. Hypericifoliae though the affinities are more so with the allopatric E. concanensis from the west coast of India.